The Effect of the Elementary Training Model on the Conventional Training Model On Kata Performance of South Sulawesi Inkanas Athletes - Same, Rahyuddin Jide; Zaum, Syahrul (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to compare the effects of the elementary training model and the conventional training model on kata performance among Inkanas athletes in South Sulawesi. A total of 60 karate athletes aged 13–18 years were selected using purposive sampling and divided equally into two groups: experimental (elementary model) and control (conventional model). The research applied a quasi-experimental method with a pretest-posttest control group design. Kata performance was assessed using the World Karate Federation (WKF) standardized criteria. The results indicated significant improvements in both groups. The experimental group’s mean score increased from 6.85 (SD = 0.75) in the pretest to 8.95 (SD = 0.62) in the posttest (p < 0.001), while the control group improved from 6.89 (SD = 0.71) to 7.55 (SD = 0.81) (p < 0.001). An independent samples t-test showed a statistically significant difference in post-test scores between the two groups (t = 6.789, p < 0.001). The findings demonstrate that the elementary training model provides superior outcomes in improving kata performance compared to conventional methods. This research suggests that incorporating structured, foundational training models can enhance skill acquisition and performance in martial arts, particularly in kata. Coaches are encouraged to adopt this approach to maximize athlete development.